The Impact of Technology on Advertising Language: A Case Study of Translation into Latvian - Ločmele, Gunta (Vertimo studijos, 2025)
Adverts are part of linguistic landscape both reflecting and influencing the processes in language. This article examines instances of code-switching in Latvian translated advertising. Code-switching in advertising appears to be topic-related: the largest number of cases seems to occur in the field of technologies due to its rapid development; however, other fields—particularly those of somewhat lesser economic significance, such as cosmetics—demonstrate it as well. English influence in advertising leads to hybridisation, orthographic changes, semantic changes, and awkward syntactic constructions, partly perpetuated by machine translation and other AI tools. Although AI technologies have improved over the period of the study, as demonstrated by several examples, human-led expertise is still required in the transcreation of advertising.
Keywords: transcreation; advertising; code-switching; linguistic landscape; machine translation; AI